2022
DOI: 10.1108/ijbm-08-2021-0383
|View full text |Cite
|
Sign up to set email alerts
|

Brand bank attachment to loyalty in digital banking services: mediated by psychological engagement with service platforms and moderated by platform types

Abstract: PurposeVarious digital banking platforms (website and apps) are offered to bank customers in order to create an experiential service, which is essential in retaining customers and generating brand bank loyalty. The current study aims to examine the dynamics of customer emotional experience generated during digital banking service delivery and investigate the effect of customer psychological engagement with various digital platform types on brand bank loyalty creation.Design/methodology/approachA conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 93 publications
0
27
1
2
Order By: Relevance
“…Building loyalty is claimed to be an important outcome of successful management of customer experience (Srivastava & Kaul, 2016). This variable was studied as outcome of OCE in such studies as for example, Cachero‐Martinez & Vazquez‐Casielles (2021), Levy (2022), Molinillo et al (2020), or Pandey and Chawla (2018).…”
Section: Results—systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Building loyalty is claimed to be an important outcome of successful management of customer experience (Srivastava & Kaul, 2016). This variable was studied as outcome of OCE in such studies as for example, Cachero‐Martinez & Vazquez‐Casielles (2021), Levy (2022), Molinillo et al (2020), or Pandey and Chawla (2018).…”
Section: Results—systematic Literature Reviewmentioning
confidence: 99%
“…Several studies have focused on comparisons between customer experience in e‐commerce and m‐commerce (e.g., Levy, 2022; Rezaei & Valaei, 2017) or between tablet versus smartphone experience (Sohn et al, 2017). They have found that customers who engage in m‐commerce exhibit improved brand experience, more favorable brand attitudes, and a higher level of brand attachment compared to those utilizing e‐commerce.…”
Section: Results—systematic Literature Reviewmentioning
confidence: 99%
“…Source : https://www.bi.go.id/id/statistik/economics of finance/ssp/uang-elektronik-sum.aspx Based on graph 1, it can be explained that the phenomenon related to the use of technology applications in the world of e-money banking for five years has increased this is due to users or customers feeling the benefits and ease of transactions. Repair digital technology in design service banking could increase response emotional customer (Levy, 2022) . Indonesian banks are adopting technology, namely information and communication technology (ICT), to automate banking procedures (Alisjahbana et al, 2020) .…”
Section: Figure 1 Circulating Electronic Money Transaction Instrumentsmentioning
confidence: 99%
“…Innovation technology contemporary this have significant impact _ profitable sector commercial , allowing banks to give more service _ good to customer (Farah et al, 2018) The application of technology applications to banking products is a transformation of existing products and made into a variety of digital media products. The literature on digital banking services mainly focuses on aspects of technology adoption (Levy, 2022) . Service digital banking has fully change how banks run the business (Ahmed et.al, 2021) .…”
Section: Figure 1 Circulating Electronic Money Transaction Instrumentsmentioning
confidence: 99%
“…The project will provide personalized and accurate weather information. The research results of this project are important for improving the level and quality of meteorological information services in China and promoting the development process of meteorology 3,4 .…”
Section: Introductionmentioning
confidence: 99%